A Glint From The Kāmasūtra in al-Ǧāḥiẓ's Kitāb Al-Ḥayawān. (2nd September 2020) - Kahl, Oliver
Abstract: This article investigates an apparent quotation from Vātsyāyana's (fl. late third century ce) Kāmasūtra in al-Ǧāḥiẓ's (d. 255/869) Kitāb al-Ḥayawān or 'Book of Animals', from its original Sanskrit form through to the guise it assumes in the Arabic text. Evidence is furnished for an oral transmission at the hands of non-literary circles, showing how a given statement's content may considerably be altered without its origins being effaced. The possibilities and limitations of identifying and tracing a vague representation of a Sanskrit saying in Arabic garb are illustrated here through a detailed case study of one extant specimen.